The song art’s representational functions in the formation of Kazakhstan’s cultural image - Begalinova G, Seisenbekov K,; Ospanova T, Bultbayeva A,; Z, Kazybekova (Opción, 2019)
The given article presents an analysis of matter, features and importance of representational functions of the song art that contributes greatly to the formation of the cultural image of the state. The methodological base of the research is the focus on the systematic, integrated approach to the examination of peculiarities of representational functions of the song art. The article points out that the creative work of modern Kazakh composers and representational functions of the song art specify the constituent part of national image. In conclusion, the historical heritage of Kazakhstan – cultural values and a unique mentality – is a powerful resource.